2022
DOI: 10.3389/fpsyt.2022.919078
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of social support and hope on quality of life via emotional distress among stroke survivors: A three-wave structural equation model

Abstract: ObjectivesStroke survivors are prone to functional impairments and reduced quality of life (QoL). This study examined the mediating role of social support and hope in the relationships between functional impairment, emotional distress, and QoL.MethodsA total of 188 stroke survivors in Hong Kong completed assessments on functional impairment, social support, and hope at baseline, with follow-up measurements of emotional distress at 2 months and QoL at 8 months. Structural equation modeling with bootstrapping wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The results of this study showed that the QoL of middle‐aged and older people with stroke was at a medium level. This was higher than the results of a study of 188 stroke patients aged 18–65 years selected by convenience sampling from hospitals, community rehabilitation centres, and patient self‐help groups conducted in Hong Kong (Fong et al., 2022). The reason may be related to the fact that the patients included in this study had their first attack, and their NIHSS scores mostly indicated mild stroke.…”
Section: Discussionmentioning
confidence: 61%
“…The results of this study showed that the QoL of middle‐aged and older people with stroke was at a medium level. This was higher than the results of a study of 188 stroke patients aged 18–65 years selected by convenience sampling from hospitals, community rehabilitation centres, and patient self‐help groups conducted in Hong Kong (Fong et al., 2022). The reason may be related to the fact that the patients included in this study had their first attack, and their NIHSS scores mostly indicated mild stroke.…”
Section: Discussionmentioning
confidence: 61%
“…46 Hope is an important psychological and spiritual resource that can protect against perceived stress, and people with higher hope levels can adopt a more positive coping approach. 47,48 We found that hope was positively correlated with the score for the GIS dimension Gout concern overall (β=0.198), meaning that hope has a negative impact on the quality of life of this dimension. This result differs from previous studies, 10,47 and the reasons for this phenomenon need to be further investigated.…”
Section: Discussionmentioning
confidence: 78%